Treatment patterns of patients with migraine eligible for anti-CGRP pathway monoclonal antibodies - Khodavirdi, Ani C.; Multani, Jasjit K.; Oh, Sam S.; Vuvu, Fiston; Bensink, Mark E.; Stockl, Karen M.; Hawkins, Kevin; Chiang, Chia-Chun; Green, A. Laine; Tepper, Stewart J. (Frontiers in Neurology, 2024)
Migraine is a debilitating neurological disorder, with a wide range of symptoms and disease burden, underscoring the heterogeneity of patients' disease characteristics and treatment needs. To characterize the profile of migraine patients in the US who may be eligible for preventive treatment with an anti-CGRP pathway mAb and to better understand treatment patterns and real-world use of acute and preventive medications for migraine, we conducted a retrospective cohort study of adult patients identified as having migraine using diagnosis codes or migraine-specific medication use (first = index) in the IQVIA PharMetrics ® Plus database. Patients were required to have ≥12 months of continuous enrollment in medical and pharmacy benefits prior to index (baseline) and after index (follow-up). Patients were stratified into chronic migraine (CM) and non-chronic migraine (non-CM) by diagnosis codes. Based on acute migrainespecific medication dispensing data in the follow-up period, non-CM patients were divided into 3 cohorts: highest, middle, and lowest tertile of total units of dispensed acute migraine-specific medication (gepants, ditans, ergot derivatives, and triptans). Migraine medication use was captured in the baseline and followup periods. 22,584 CM and 216,807 non-CM patients (72,269 patients in each tertile) were identified and included in the study. Over the follow-up, CM patients had a mean of 70 units of acute migraine-specific medications dispensed, while the highest, middle, and lowest tertile of non-CM patients had a mean of 92, 29, and 10 units, respectively. Anti-calcitonin gene-related peptide pathway mAbs were dispensed for 28.9% of CM patients, and for 6.9%, 4.1%, and 2.9% of non-CM patients in the highest, middle, and lowest tertiles, respectively. A lower proportion of non-CM patients had use of anti-calcitonin gene-related peptide pathway mAbs compared to CM patients, confirming the unmet need with appropriate preventive medication. There appears to be a persistent gap in management of patients without a diagnosis of CM who are dispensed high quantities of acute migraine-specific medications.